divide and simplify (3x-21/121) / (w-7/33w)

(3x-21/121) / (w-7/33w) =(11979x-693)/(3146w) =1089x-63)/286w

Question

Asked 3/21/2012 5:10:16 PM

Updated 6/30/2014 1:35:32 AM

1 Answer/Comment

Rating

3

(3x-21/121) / (w-7/33w)

=(11979x-693)/(3146w)

=1089x-63)/286w

=(11979x-693)/(3146w)

=1089x-63)/286w

Added 6/30/2014 1:35:32 AM

This answer has been confirmed as correct and helpful.

solve for v.... 6/v=9/v-1/2

Question

Expert Answered

Updated 9/20/2014 10:57:20 PM

2 Answers/Comments

6/v=9/v-1/2

6/v - 9/v = -1/2

-3/v = -1/2

v = -3/( -1/2)

v= -3 *(-2)

v = 6

6/v - 9/v = -1/2

-3/v = -1/2

v = -3/( -1/2)

v= -3 *(-2)

v = 6

Added 9/20/2014 10:56:18 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [9/20/2014 11:00:45 PM]

multiply... (4x+4)(6x^2 +8x+3) **Weegy:** a.
Factor as:
(x - 3)(x + 1)^3 = 0
zeros are at x = 3 and x = -1
y ' = 4x^3 - 12x - 8
4(x - 2)(x + 1)^2
zeros at x = 2 and x = -1
- - - - - - - - - - - - - - - - - - - -
b.
y " = 12x^2 - 12
y "(2) = 36 which is positive, [ so x = 2 is a minimum point
y "(-1) = 0, an inflection point
- - - - - - - - - - - - - - - - - - - -
c.
f(x) decreases from [-8, 2] and increases from [2, +8]
- - - - - - - - - - - - - - - - - - - -
d.
f(x) is negative for x = [-1, 3] and positive for all other real values ] (More)

Question

Expert Answered

Updated 3/21/2012 11:26:01 AM

3 Answers/Comments

(4x+4)(6x^2 +8x+3) = 24x^3 + 56x^2 + 44x + 12

Added 3/20/2012 10:42:09 AM

This answer has been confirmed as correct and helpful.

Unflagged by andrewpallarca [7/7/2014 7:25:01 PM], Confirmed by andrewpallarca [7/7/2014 7:25:03 PM]

factor completely... 4x^8 - 12x^7 + 24x^6
**Weegy:** 4x^8 - 12x^7 + 24x^6
= 4x^6 (x^2 - 3x + 6) (More)

Question

Expert Answered

Updated 7/11/2014 12:10:08 AM

0 Answers/Comments

subract the polynomials (-9s^2 + 5s + 2) - (7s^2 + 2) **Weegy:** (-9s^2 + 5s + 2)- (7s^2 + 2)
= (-9s^2 + 5s + 2) + (-7s^2 - 2)
= -16s^2 + 5s
(More)

Question

Expert Answered

Updated 182 days ago|2/16/2018 1:30:28 PM

0 Answers/Comments

factor the trinomial. a^3 - 2a^2 -15a

Question

Not Answered

Updated 169 days ago|2/28/2018 7:46:02 PM

1 Answer/Comment

a^3 - 2a^2 -15a

= a(a^2 - 2a - 15)

= a(a + 3)(a - 5)

= a(a^2 - 2a - 15)

= a(a + 3)(a - 5)

Added 169 days ago|2/28/2018 7:46:02 PM

This answer has been confirmed as correct and helpful.

27,197,783

questions answered

There are no comments.